Gut-skin-axis modulation via fecal microbiome transplant. An ecological approach for atopic dermatitis treatment. - Ursia, Catharina Clarissa; Putri, Patricia Dian (Journal of Pakistan Association of Dermatologists, 2023)
There are numerous factors underlying the development and severity of atopic dermatitis (AD) and the skin barrier is central in its pathogenesis. Maintaining a strong skin barrier is principle in the management of AD and this may be achieved via immunomodulation of the skin barrier. Gut-skin-axis has long been established and is cardinal in skin barrier immune regulation. There is a growing body of evidence in the use of fecal microbiome transplant (FMT) to engraft immunomodulating microbiome from healthy persons thus restoring gut microbiome balance. The restoration of microbiome homeostasis leads to the restoration of the systemic and gut-skin-axis immunomodulation. FMT has demonstrated its efficacy in conditions such as recurrent Clostridium difficile infection (rCDI), autoimmune disorders, and Chron’s disease which is strongly correlated to AD. This paper is made by reviewing publications related to fecal microbiome transplant and atopic dermatitis in order to further elaborate its potential use in the management of AD.